HUBUNGAN ANTARAPENGETAHUAN DAN SIKAP DENGAN TINDAKAN HIDUP SEHAT PASIEN TB PARU DI POLIKLINIK PARU RSUP PROF DR. R. D KANDOU MANADO - Simak, Valen F; Pangemanan, Damajanty H.C.; Untu, Frenly Muntu (Universitas Sam Ratulangi)
Abstract: Pulmonary tuberculosis is disease cause of death to 3 in indonesia. Prevalence pulmonary tuberculosis in indonesia is now 555,000 cases ( 256 cases/ 100,00 inhabitants ), and 46 % of them was new cases. The act of healthy living one may stir in various factors such knowledge and attitude.Research Purposes Knowing the relation between knowledge and attitude with the act of healthy living patient pulmonary tuberculosis in the polyclinic pulmonary RSUP Prof Dr. R. D. Kandou Manado.Design this researchis descriptive analytic the plan cross sectional. The selection of Samples with purposive sampling as many as 97 respondents. Next the data obtained were analyzed with the program the computerized Statistical Product and Service Solutions (SPSS) version 20.0 by using the chi-square test (x2), at the level of significance 95% (Î± 0,05).Statistical analyses showing the result that there is a relationship between knowledge by the action of living healthy patient pulmonary tuberculosis in the polyclinic pulmonary RSUP Prof. Dr. R. D. Kandou Manado, p = 0,000 (p<0,05). Is no link between an attitude with the act of healthy living patient pulmonary tuberculosis in the polyclinic pulmonary RSUP Prof. Dr. R. D. Kandou Manado, p = 0,011 (p<0,05).Conclusions, knowledge and attitude having relation meaningful with the act of healthy life.Advise, the need for an increase in knowledge and attitudes about healthy life to to improve the quality of life of a person. For the world in nursing to research can be used as material for carrying out the promotion of health (counseling) for people who suffer pulmonary tuberculosis and not with based on duties and functions of a nurse namely as a edukator. Key words:Knowledge,Attitude, Healthy Living Actions, Pulmonary tuberculosis Abstrak: Tuberkulosis paru merupakan penyakit penyebab kematian ke 3 di Indonesia. Prevalensi tuberkulosis paru di Indonesia mencapai 555.000kasus (256 kasus/100.000 penduduk),dan 46% diantaranya merupakan kasusbaru. Tindakan hidup sehat seseorang dapat di pengaruhi berbagai faktor antara lain pengetahuan dan sikap. Tujuan PenelitianMengetahui hubungan antarapengetahuan dan sikap dengan tindakan hidup sehat pasien TB Paru di Poliklinik Paru RSUP Prof Dr. R. D. Kandou Manado. Desain Penelitianini adalah deskriptif analitik dengan rancangan cross sectional. Pemilihan sampeldengan purposive sampling sebanyak 97 responden. Selanjutnya data yang diperoleh dianalisis dengan program komputerisasi Statistical Product and Service Solutions(SPSS) versi 20.0 dengan menggunakan uji chi-square (x2), pada tingkat kemaknaan 95% (Î± 0,05).Analisis statistik menunjukan hasil bahwaada hubunganantara pengetahuan dengan tindakan hidup sehat pasien TB paru di poliklinik paru RSUP Prof. Dr. R. D. Kandou Manado, p = 0,000 (p<0,05). Ada hubunganantarasikapdengan tindakan hidup sehat pasien TB paru di poliklinik paru RSUP Prof. Dr. R. D. Kandou Manado, p = 0,011 (p<0,05).Kesimpulan, pengetahuan dan sikap memiliki hubungan yang bermakna dengan tindakan hidup sehat.Saran, perlunya peningkatan pengetahuan dan sikap tentang hidup sehat guna untuk meningkatkan kualitas hidup seseorang. Bagi dunia keperawatan agar penelitian dapat dijadikan sebagai bahan untuk melaksanakan promosi kesehatan (penyuluhan) bagi masyarakat yang menderita TB paru maupun yang tidak dengan berpatokan pada tugas dan fungsi perawat yaitu sebagai edukator. Kata kunci: Pengetahuan,Sikap, Tindakan Hidup Sehat, Tuberkulosis Paru